2011
DOI: 10.1016/j.jcf.2010.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Lung deposition of inhaled tobramycin with eFlow rapid/LC Plus jet nebuliser in healthy and cystic fibrosis subjects

Abstract: eFlow rapid reduces the nebulisation time of tobramycin and can potentially improved compliance in patients with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 23 publications
3
45
0
3
Order By: Relevance
“…Indeed, the proportion of the dose reaching the lungs was high compared with the classical nondrug targeting nebulizers. 25,26 It is consistent with a previous study with 6 subjects with ␣1-penetration index deficiency. 27 This improved efficiency is probably related to the electronically guided inspiration 25 and to the low breathing frequency 15 generated by the Akita, which are known to be beneficial for lung deposition and to target the peripheral lung as a region of interest.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the proportion of the dose reaching the lungs was high compared with the classical nondrug targeting nebulizers. 25,26 It is consistent with a previous study with 6 subjects with ␣1-penetration index deficiency. 27 This improved efficiency is probably related to the electronically guided inspiration 25 and to the low breathing frequency 15 generated by the Akita, which are known to be beneficial for lung deposition and to target the peripheral lung as a region of interest.…”
Section: Discussionsupporting
confidence: 92%
“…Mesh nebulizers were compared with conventional jet nebulizers with mains-powered compressors in Figure 1. The results of the in vivo studies in Figure 1 [44,[50][51][52][53][54][55][56][57] suggest that lung deposition is also similar for both types of nebulizers. For instance, when an aerosol with a mass median diameter (MMD) of 3 μm was produced by both a mesh nebulizer and a jet nebulizer, the lung deposition was 80% of the delivered dose.…”
Section: Mesh Nebulizers Versus Jet Nebulizers In Vivomentioning
confidence: 99%
“…It is a highly efficient nebulizer that provides approximately 90% of the nominal dose in a short treatment duration. Recent studies showed that the eFlow can improve patient compliance due to short nebulization time (33). Also, the eFlow has a range of optimal fill volumes up to 4 ml and can be used with a variety of drug formulations, such as highly viscous fluids, proteins, peptides, suspensions, and surfactants.…”
Section: Active Mesh Nebulizersmentioning
confidence: 99%